2020
DOI: 10.1017/wet.2020.91
|View full text |Cite
|
Sign up to set email alerts
|

Management of glyphosate-resistant Palmer amaranth (Amaranthus palmeri) in 2,4-D–, glufosinate-, and glyphosate-resistant soybean

Abstract: Glyphosate-resistant (GR) Palmer amaranth is a problematic annual broadleaf weed in soybean production fields in Nebraska and many other states in the United States. Soybean resistant to 2,4-D, glyphosate, and glufosinate (Enlist E3TM) has been developed and was first grown commercially in 2019. The objectives of this research were to evaluate the effect of herbicide programs applied PRE, PRE followed by (fb) late-POST (LPOST), and early-POST (EPOST) fb LPOST on GR Palmer amaranth control, density, and biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Herbicides applied PRE fb glufosinate reduced MHR Palmer amaranth density by at least 87% in 2018 and 2019. Similar findings were reported by Shyam et al (2021) and Norsworthy et al (2016). Glufosinate applied alone reduced MHR Palmer amaranth density 89% and 58% in 2018 and 2019, respectively, whereas glufosinate mixed with isoxaflutole reduced density by 63% to 100% in 2018, and 85% to 94% in 2019 (Table 4).…”
Section: Palmer Amaranth Density and Biomasssupporting
confidence: 84%
See 1 more Smart Citation
“…Herbicides applied PRE fb glufosinate reduced MHR Palmer amaranth density by at least 87% in 2018 and 2019. Similar findings were reported by Shyam et al (2021) and Norsworthy et al (2016). Glufosinate applied alone reduced MHR Palmer amaranth density 89% and 58% in 2018 and 2019, respectively, whereas glufosinate mixed with isoxaflutole reduced density by 63% to 100% in 2018, and 85% to 94% in 2019 (Table 4).…”
Section: Palmer Amaranth Density and Biomasssupporting
confidence: 84%
“…Glufosinate mixed with isoxaflutole controlled Palmer amaranth 92% to 95% in 2018 and 85% to 94% in 2019 (Table 3). Shyam et al (2021) reported 88% Palmer amaranth control 14 DAEPOST with glufosinate. Conversely, found that glufosinate in single and sequential applications provided 53% to 76% and 56% to 77% waterhemp control, respectively.…”
Section: Palmer Amaranth Controlmentioning
confidence: 99%
“…Reduced control of Palmer amaranth with dicamba applied alone in 2019 can be attributed primarily to the shorter residual control by dicamba compared to other PRE herbicide programs evaluated as observed by Hedges et al (2019). Efficacy of premixed and tank-mixed PRE herbicides with multiple effective sites of action on Palmer amaranth control were previously evaluated in soybean fields in Nebraska, with Striegel et al (2020) and Shyam et al (2021) reporting 93% to 99% control 14 and 28 DAPRE. Results from the current study are similar to those reported by Meyer et al (2015), when flumioxazin/pyroxasulfone, metribuzin, dicamba, S-metolachlor, S-metolachlor/ fomesafen, acetochlor, isoxaflutole, and S-metolachlor/mesotrione applied PRE provided 95% to 99% control of Palmer amaranth 21 DAPRE in field experiments conducted in Arkansas, Illinois, Indiana, Missouri, Nebraska, and Tennessee.…”
Section: Palmer Amaranth Controlmentioning
confidence: 99%
“…In a 2-yr study in Nebraska, Striegel et al (2020) reported that quizalofop can be applied for selective control of glyphosate/glufosinate-resistant volunteer corn in corn resistant to FOPs. Multiple HR soybean traits have been developed that enable use of phenoxy herbicides such as 2,4-D or dicamba in a mixture with glyphosate (Byker et al 2013;Shyam et al 2021). Growers prefer to mix 2,4-D or dicamba with ACCase inhibitors, assuming this mixture will provide broad-spectrum weed control; however, it can antagonize grass weed control (Blackshaw et al 2006;Underwood et al 2016).…”
Section: Management Of Herbicide-resistant Corn Volunteersmentioning
confidence: 99%
“…Multiple HR crops have been developed and commercialized in recent years, including glyphosate/dicamba-or 2,4-D-resistant soybean and cotton, glyphosate/glufosinate-resistant corn, and 2,4-D/glufosinate/glyphosate-resistant corn primarily for control of GR weeds (Beckie et al 2019). Shyam et al (2021) reported herbicide programs for effective control of GR Palmer amaranth (Amaranthus palmeri S. Watson) in 2,4-D/glufosinate/glyphosate-resistant soybean. A few other studies reported greater control of GR weeds in multiple HR soybean (Byker et al 2013;Vink et al 2012;Yadav et al 2020).…”
Section: Introductionmentioning
confidence: 99%